As repercussões do Plano LangevinWallon no Brasil - nas décadas seguintes à sua elaboração - Mortarello, Luciana Cicutto (2021)
This research aims to study the repercussions of the Plan Langevin-Wallon proposals in Brazil, in the decades following its elaboration, that is, in the 1950s and 1960s. For data collection, two sources were used: editions of Revista Brasileira de Estudos Pedagógicos – RBEP (Brazilian Magazine of Pedagogical Studies) and teachers’ testimony. In the RBEP editions, between the years 1949 and 1958, references to the Plan Langevin-Wallon were found in texts that addressed, mainly, the elaboration of the first proposal of the Law of Directives and Bases of Education for Brazil, the renovation of secondary education and the introduction of experimental classes, movement started in Brazil from the 1950s. Expanding the research on the renewal of secondary education and the implantation of experimental classes, a movement that began in Brazil in the 1950s, it was observed that there was a strong influence of the “Centre international d'études pédagogiques”- CIEP and of the “Classes Nouvelles”, both based in France and created as part of the Plan Langevin-Wallon, in 1945, to promote and experiment with its proposals. Among the actions promoted for the implantation of the experimental classes in Brazil, there was, with the support of the Brazilian Ministry of Education and Culture, in partnership with CIEP, an exchange program between French and Brazilian teachers. Due to the exchange program, it was possible for Brazilian teachers to carry out an internship at CIEP, in Sèvres. From this observation, the importance of listening to teachers who experienced this moment of search during the exchange program, in Sèvres, also became evident for the renewal of teaching. According to this research and after analyzing the mention to the Plan Langevin-Wallon in RBEP and in the testimonies, it was possible to conclude that the Plan Langevin-Wallon was present in all moments of the search for the renewal of teaching, as well as in the dissemination of renovation ideas, promoted by RBEP, in the debates and discussions promoted by the Pedagogical Study Centers, through the exchange program between Brazilian and French educators, in the implementation of the first experimental classes created by Luis Contier, in the legal approval for the implementation of new experiences, and, finally, in the implementation of experimental classes that followed, as evidenced the pedagogical matrixes of the “Nouvelles Classes”. Throughout the movement for renewal, the Langevin-Wallon Plan was an inspiration, reference and model, after all, its proposals envisioned a teaching that allowed the well-being of students, respecting their aptitudes, capacities and individualities, that is, proposals that aimed at construction of a new man and, therefore, a new society